An investigation of bamboo-strip constructions built according to Yona Friedman's manuals. Issue 2 (1st April 2022) - Chiacchiera, Paolo; Bocco, Andrea; Ceretto, Walter; Ghirardotti, Davide
Abstract : This paper describes a research study on the structural and constructional properties of bamboo strips used in accordance with manuals to improve the quality of self-building authored by Yona Friedman. To investigate these properties, four full-scale roof structures of different designs were built and tested to find their maximum load, deformation behaviour and failure. Two of these structures were subsequently rebuilt to explore strengthening possibilities that were assessed through further tests, which showed an increase of maximum load. Besides field tests, the bamboo roofs were modelled using finite-element analysis software in order to evaluate the correspondence between experimental and analytical data. The results showed remarkable differences between the actual behaviour of the structures and that obtained from the modelling due to the dimensional unevenness of strips and the imperfect execution of lashed joints, with the latter not always allowed to obtain the ideal hinge bearing condition hypothesised in the analytical model.